The global financial crisis and Asia implications and challenges - Kawai, Masahiro, 1947-; Lamberte, Mario B.; d (Oxford : Oxford University Press, 2012)
This text demonstrates how Asian countries tried to minimize the impact of the global financial crisis, identifies structural weaknesses in their economies, and discusses policy options for strengthening Asian economies to avoid future crises and promote sustainable growth in the long-term.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Asia -- Economic conditions -- 21st century; Asia -- Economic policy; Global Financial Crisis, 2008-2009.